Implementasi Corporate Social Responsibility sebagai Keunggulan Kompetitif Perusahaan - Arief Rahman (Sinergi: Kajian Bisnis dan Manajemen, 2004)
This article presents the re-emergence of Corporate Social Responsibility (CSR) concept which nowadays become a positive trend in business world to use it as a source of sustainable competitive advantage. The concept has been re-emerging because of factors of globalisation, technology and media revolution, and terrorist attacks. This article also pre¬sents some parties which have capability to endorse business to implement CSR, such as gov¬ernment, community as well as business organizations, corporation itself and society. And in order to bring unimpair description, this article describes the implementation of CSR as cor¬porate strategic competitive advantage in Vodafone and Thiess. Keywords: corporate social responsibility, triple bottom line, competitive advantage, sustainable development, strategic management